2009
DOI: 10.1016/s1658-3876(09)50009-x
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the Fischer scoring system and the Breast Imaging Reporting and Data System in identification of malignant breast lesions

Abstract: The MRM BI-RADS lexicon using the Fischer scoring system is useful and has a high predictive value, especially for malignant breast lesions, and is easy to apply. Overlapping features between benign inflammatory and malignant lesions might yield a reduced accuracy in inflammatory pathologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Al-Khawari et al and Tozaki et al showed in their studies that most malignant lesions had diffuse and irregular shape while benign lesions had round or oval shape (16,17).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Al-Khawari et al and Tozaki et al showed in their studies that most malignant lesions had diffuse and irregular shape while benign lesions had round or oval shape (16,17).…”
Section: Discussionmentioning
confidence: 97%
“…This is comparable with Al-Khawari et al who reported that most malignant lesions showed ill defined margin while benign lesion showed well defined margin. They also reported that the value of morphologic criteria in the form of shape and margin of the lesion to describe MRI-detected breast lesions has been limited by the lack of a definitive classification scheme (16).…”
Section: Discussionmentioning
confidence: 99%
“…In our study ultrasonography finding of speculated masses was found to be the feature with the most potential in differentiating malignant lesions from benign with sensitivity 44.4% and specificity 100.0%. As Al-Khawari et al, and Tozaki and Igarashi [11,12] showed in their studies that most malignant lesions had diffuse and irregular shape while benign lesions had round or oval shape.…”
Section: Discussionmentioning
confidence: 89%